Prevalence Risk Factors and Management of Dry Eye Disease in The Academic Hospital of Riyadh Saudi Arabia - Hayat Alzahrani; Maryam Alharbi; Gharam Alanazi; Najd AlKhudhairy; Raneem Alqahtani; Bader AlMehmadi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background and Objectives: Dry eye disease is highly prevalent in Arab countries. The study aims to measure the prevalence of dry eye syndrome in Primary Health care settings at King Abdullah bin Abdulaziz University Hospital. To determine the incidence of risk factors with dry eye syndrome, in addition to the effective different therapeutic modalities for dry eye syndrome, finally to assess the patient’s satisfaction with their treatment. Materials and Methods: A cross-sectional study was conducted among patients who attended the outpatient department (OPD) of King Abdullah bin Abdulaziz University Hospital (KAAUH), Riyadh, Saudi Arabia, in 2022. The study used Dry Eye Epidemiologic Projects (DEEP) and the Dry Eye Treatment satisfaction module questionnaire to evaluate the study objectives. Statistical analysis was carried out using RStudio (R version 4.1.1). Results: The final analysis was conducted on 358 participants. Most were females (73.2%) and Saudis (98.6%). The prevalence of DED in our study was 31.0% (95%CI, 26.3 to 36.1). Based on the multivariate analysis, the female gender (OR=4.49, 95% CI, 1.86 to 11.8, p = 0.001), medication use (OR=2.25, 95% CI, 1.22 to 4.15, p = 0.009) and a history of eye surgery (OR=2.28, 95% CI, 1.25 to 4.16, p = 0.007) were independent risk factors for dry eye disease among the participants. Regarding satisfaction with treatment effectiveness, more than half of the respondents agreed or strongly agreed that the treatment relieved most of the DED symptoms (58.5%) and was happy with how quickly the treatments worked. Conclusions: In conclusion, female gender, use of medication, and history of eye surgery were identified risk factors for DED. There was an increased prevalence of DED residents of Riyadh in our study. Further prospective clinical studies should be conducted to evaluate the risk factor and causes of increased prevalence in the kingdom.